EARNINGS MANAGEMENT IN CORPORATE GOVERNANCE: A SYSTEMATIC LITERATURE REVIEW - Wardani, Mellinda Sri; Saribu, Yolanda Angel Sabatani Dolok; Kesuma, Sambas Ade (UTSAHA: Journal of Entrepreneurship, 2023)
Increased profits will attract shareholders. In order to attract their attention, companies will conduct various ways about the financial health and company performance that are available in the public domain before they are publicized. Therefore, the company has the motivation to implement earnings management that can increase profits to improve its performance results. Therefore, this research aims to determine the impact of earnings management on corporate governance. This research method used a systematic literature review with Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines for articles that have been published during 2010-2023. Around 170 articles were obtained from journal databases, such as Emerald Insight, Scopus, Science Direct, and others. Furthermore, data validation and testing were conducted to obtain 50 articles that could be used as the main research. The main point of this literature study is to examine the earnings management function in corporate governance in various published articles.